Pengetahuan dan Kemampuan Penderita Hipertensi tentang Pemanfaatan Kompres Jahe - Sanny Frisca; Dheni Koerniawan; Tri Widyastuti (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
Headache and stiff neck can feel with people with hypertension, that condition can make patient uncomfortable. Ginger compress at head and neck can reduce pain in both because ginger contain of gingerol and shogaol which can make vasodilation and reduce inflammation. There is still few patient who use ginger for reduce pain because patient lack of information of that. In the other hand, education as nursing intervention can use to improve patient knowledge and ability to giving ginger compress. This study, measure impact of education with giving questionner and observe respondent ability and then analyse the data with Wilcoxon Signed Rank Test. The result shown education which give to 35 respondent can improve patient knowledge and ability significantly with p-value 0,000 and recommend this intervention to enhance patient knowledge and ability.